SISTEM PENENTUAN POSISI WAKTU NYATA (REAL TIME ) KENDARAAN NIAGA - Pertiwi Ayu (Semantik, 2011)
Real time positioning system for commercial vehicle companies that rely on vehicles intended as a means of product delivery transportation. The system is divided into two parts, the process that handles the login and the process that handles generate reports. The method used to complete the development process is a RAD (Rapid Application Development). The advantage gained from the use of this system is that users can view while controlling the presence location of the vehicle niaganya. So the management can take a decision to process the work efficiency of the generated report.